فعالية استخدام استراتيجية Active Knowledge Sharing لترقية مهارة الكتابة لطلاب الفصل السابع بمدرسة الثانوية الإسلامية السلام بانجيلان توبان - Najikha, Azifatun; Sholehan, Sholehan; Syafi’i, Syafi’i (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
Learning strategies are one effective way to achieve learning goals. Writing skills are skills that are quite difficult to learn by students, especially in expressing thoughts in written form due to less mastery of Arabic vocabulary and difficulties in composing sentences using the correct Arabic rules. Therefore, the strategy of active knowledge sharing is used as a strategy that can improve students Arabic writing skills. This research was cinducted at the Madrasah Tsanawiyah Assalam Bangilan Tuban by using class VII-B as the sample. This research method used in this study is a quantitative method using observation, documentation interviews, tests and questionnaires as data collection techniques. This study aims to determine the effectiveness of the use of active khowledge sharing strategies in improving Arabic writing skills of Assalam Bangilan Tuban Madrasah Tsanawiyah students.